Sensory screening of pea (Pisum sativum L.) seeds and correlations to seed quality - Bjørn Dueholm; Åsa Grimberg; Mohammed Hefni; Cornelia Witthöft; Gun Hagström; Cecilia Hammenhag (Future Foods, 2025)
Growing demand for environmentally sustainable protein sources is shifting dietary preferences toward plant-derived alternatives such as legumes. Pea (Pisum sativum L.) seeds offer great potential for expanded human consumption, but sensory quality is key for consumer acceptance and cultivar development. In this study, a diversity panel of 15 pea accessions was evaluated for nutrients and phytochemicals (protein, resistant and non-resistant starch, fatty acids, choline, phytate, saponins, and sucrose) and their sensory attributes (taste, aroma, mouthfeel, and aftertaste). Among the sensory attributes, mouthfeel and aroma contributed most to the variation. Principal component analysis revealed two large, distinct clusters, primarily separated by seed coat (testa) colour. Accessions with a dark-coloured testa were generally perceived more odour intense and with more texture, while accessions with light-coloured testa were sweeter and juicier. Accessions with wrinkled seeds stood out in their content of non-resistant starch, sucrose, total choline, and phytate, when compared to smooth and dimpled seeds. Shorter cooking times were positively correlated to the perception of higher bitterness. This study highlights the potential in combining seed compositional analysis and sensory evaluations for screening pea accessions suitable for the development of future food products.